Proximal tubular bicarbonate reabsorption and PCO2 in chronic metabolic alkalosis in the rat. - Maddox, D A; Gennari, F J (The Journal of Clinical Investigation, 1983)
Studies were undertaken to define the pattern of proximal tubular bicarbonate reabsorption and its relation to tubular and capillary PCO2 in rats with chronic metabolic alkalosis (CMA). CMA was induced by administering furosemide to rats ingesting a low electrolyte diet supplemented with NaHCO3 and KHCO3. Proximal tubular bicarbonate reabsorption and PCO2 were measured in CMA rats either 4-7 or 11-14 d after furosemide injection, in order to study a wide range of filtered bicarbonate loads. A group of nine age-matched control animals, fed the same diet but not given furosemide, was studied for comparison. In a third group of controls, the filtered load of bicarbonate was varied over the same range as in the CMA rats by plasma infusion and aortic constriction. The CMA rats had significant alkalemia and hypokalemia (4-7 d: pH 7.58, HCO3 38.3 meq/liter, K+ 2.1 meq/liter; 11-14 d: pH 7.54, HCO3 38.1 meq/liter, K+ 2.5 meq/liter). Nonetheless, proximal bicarbonate reabsorption was not significantly different from that seen in control rats at any given load of filtered bicarbonate (from 250 to 1,300 pmol/min). In both control and CMA rats, 83-85% of the filtered bicarbonate was reabsorbed by the end of the accessible proximal tubule. These observations indicate that proximal bicarbonate reabsorption is determined primarily by the filtered load in chronic metabolic alkalosis. When single nephron glomerular filtration rate (SNGFR) is reduced by volume depletion in the early postfurosemide period, the filtered load and the rate of proximal bicarbonate reabsorption remain at or below control levels, maintaining metabolic alkalosis. In the late postfurosemide period, however, SNGFR returned to control levels in some instances. In these animals, both the filtered load and rate of proximal reabsorption were increased above the highest levels seen in control animals. The PCO2 gradient between the peritubular capillaries and arterial blood (Pc-Art) was significantly higher in CMA than in control, even though the rate of proximal bicarbonate reabsorption did not differ. Thus, proximal bicarbonate reabsorption did not appear to be the primary determinant of Pc-Art PCO2. PCO2 in the early proximal (EP) tubule was significantly higher than in either the late proximal (LP) tubule or peritubular capillaries in both control and CMA rats. The EP-LP PCO2 gradient correlated directly with proximal bicarbonate reabsorption (P less than 0.05). The small elevation in PCO2 in EP may be related to CO2 generated at this site in the process of bicarbonate reabsorption.